A Review of Actuation and Sensing Mechanisms in MEMS-Based Sensor Devices - Algamili, Abdullah Saleh; Khir, Mohd Haris Md; Dennis, John Ojur; Ahmed, Abdelaziz Yousif; Alabsi, Sami Sultan; Ba Hashwan, Saeed Salem; Junaid, Mohammed M. (Nanoscale research letters, 2021)
Over the last couple of decades, the advancement in Microelectromechanical System (MEMS) devices is highly demanded for integrating the economically miniaturized sensors with fabricating technology. A sensor is a system that detects and responds to multiple physical inputs and converting them into analogue or digital forms. The sensor transforms these variations into a form which can be utilized as a marker to monitor the device variable. MEMS exhibits excellent feasibility in miniaturization sensors due to its small dimension, low power consumption, superior performance, and, batch-fabrication. This article presents the recent developments in standard actuation and sensing mechanisms that can serve MEMS-based devices, which is expected to revolutionize almost many product categories in the current era. The featured principles of actuating, sensing mechanisms and real-life applications have also been discussed. Proper understanding of the actuating and sensing mechanisms for the MEMS-based devices can play a vital role in effective selection for novel and complex application design.